Pembinaan Kebermaknaan Hidup melalui Bimbingan dan Konseling Keagamaan pada Lansia di Panti Wreda Siti Khadijah Cirebon: Development of Meaningful Life through Guidance and Counseling Religion in the elderly at the Siti Khadijah Nursing Home, Cirebon - istiqomah; Rina Kurnia Rina (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Old age (elderly) is the last period of development in human life. Getting old issomething that cannot be avoided. When entering the old age period, becomingsomeone who is more meaningful in life seems very important. The elderly willface various problems related to changes in physical, cognitive andpsychosocial aspects. this will cause various impacts, one of which is the feelingof meaninglessness in life. Therefore, religion plays an important role indirecting them to interpret life truly. Life will be meaningful if religion is usedas a guide. Thus religious guidance for old age is very important because it givesparents old age to realize themselves as whole human beings in order toachieve happiness in life in this world and the hereafter. This service aims tofind out and provide an understanding of the description of the meaning of lifein the elderly, provide religious counseling guidance to increase themeaningfulness of the lives of the elderly and their impact on themeaningfulness of the lives of the elderly. This service uses a qualitativenarrative approach through 3 stages: initial observation, implementationreligious guidance and counseling, and measurement of the meaning of life. Thepopulation in this service is the elderly who live in the Cirebon Nursing Home.The sampling technique used is saturated sampling. Sampling using totalsampling method as many as 4 elderly. Measurement of the meaningfulness oflife in the elderly was carried out using a questionnaire in the form of a Likertscale and an interview guide. The results of the service, after carrying outreligious counseling guidance for the elderly at the Kasih Ibu Nursing HomeCirebon have a meaningful life in terms of aspects of freedom of will, aspects ofthe will to meaning and aspects of the meaning of life experience changessignificant with the average increase in the category to be high.